2022
DOI: 10.3390/foods11243979
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Characteristics, Purchasing Preferences and Willingness to Consume Organic Food: A Cross-Location Comparison of Nine Cities in Central Ecuador

Abstract: Agriculture worldwide faces the need to reduce chemical pesticides and produce healthier food. In Latin America, research on the organic food sector primarily focuses on supply. Consumption analysis is crucial for providing information about customers’ needs. This paper aims to analyze the Ecuadorian organic food sector, which is an interesting case for investigating the relationship between willingness to consume organic food and socioeconomic factors. To this end, 382 consumers were surveyed. The study appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The price difference between organic and conventional fruit is one of the main obstacles to the spread of this type of product worldwide, as confirmed in this study and those by other researchers [61,62]. The results of the study presented here clearly indicate the growing reluctance of consumers to accept increasing price differences.…”
Section: Discussionsupporting
confidence: 85%
“…The price difference between organic and conventional fruit is one of the main obstacles to the spread of this type of product worldwide, as confirmed in this study and those by other researchers [61,62]. The results of the study presented here clearly indicate the growing reluctance of consumers to accept increasing price differences.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, reviews of the literature draw attention to the dearth of research on green product consumption in regions like Ecuador and Peru. The studies from these countries have similarly leaned on quantitative methods, predominantly relying on self-administered questionnaires for gathering data [7,12,17,[37][38][39][40][41]. This trend is corroborated by various review articles that note the reliance on self-reported measures within the field of green consumption research [25,32].…”
Section: Introductionmentioning
confidence: 99%